The Relationship Between Caffeine Consumption and The Incidence of Depression, Anxiety and Stress in Online Motorcycle Taxi Workers in Mataram City - Nurul Inayah Tajuddin Putri; Lusiana Wahyu Ratna Wijayanti; Iing Iing; Nisia Putri Rinayu (CV. Inara, 2026)
Mental health problems such as depression, anxiety, and stress are increasingly experienced by informal sector workers, including online motorcycle taxi drivers. Long working hours and high work pressure encourage high caffeine consumption to maintain alertness, which may affect mental health. This study aimed to determine the relationship between caffeine consumption and the incidence of depression, anxiety, and stress among online motorcycle taxi workers in Mataram City. This study was an observational analytic study with a cross-sectional design involving 109 online motorcycle taxi workers selected using purposive sampling. Data were analyzed using univariate and bivariate analysis with the Spearman Rho test. The results showed that most respondents had very high caffeine consumption. Depression levels were generally normal, while anxiety and stress showed moderate to high prevalence. There was no significant relationship between caffeine consumption and depression (r = 0.090; p = 0.351). However, caffeine consumption showed a significant positive relationship with anxiety (r = 0.280; p = 0.003) and stress (r = 0.523; p = 0.000). In conclusion, high caffeine consumption is associated with increased anxiety and stress, but not with depression among online motorcycle taxi workers in Mataram City.